(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This article examines the research of foreign scientists on how blended learning allows students to develop independent work skills and increase motivation for learning, preparing students for research activities, and also examines the trends and advantages of blended learning in higher education.